2013
DOI: 10.1002/bimj.201200012
|View full text |Cite
|
Sign up to set email alerts
|

Confidence interval estimation of the difference between two sensitivities to the early disease stage

Abstract: Although most of the statistical methods for diagnostic studies focus on disease processes with binary disease status, many diseases can be naturally classified into three ordinal diagnostic categories, that is normal, early stage, and fully diseased. For such diseases, the volume under the ROC surface (VUS) is the most commonly used index of diagnostic accuracy. Because the early disease stage is most likely the optimal time window for therapeutic intervention, the sensitivity to the early diseased stage has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For future work, following the same vein of Dong et al (2014), we would like to develop the semi-parametric inference procedure for the difference of two correlated P 2 ’s, based on the empirical likelihood technique.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For future work, following the same vein of Dong et al (2014), we would like to develop the semi-parametric inference procedure for the difference of two correlated P 2 ’s, based on the empirical likelihood technique.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Note that the transformation parameters λ 1 and λ 2 have to be estimated by the data; hence, their variability must be taken into account. This issue is usually ignored in the literature when the Box‐Cox is considered (see the work of Dong et al among others). The underlying likelihood is of the form alignleftalign-1Lpfalse(λ1,2false)align-2=i=1nA12πdetΣAfalse(λ1,2false)exp12W1Ai(λ1)μ1A(λ1),W2Ai(λ2)μ2A(λ2)boldΣA(λ1,2)1W1Ai(λ1)μ1A(λ1),W2Ai(λ2)μ2A(λ2)align-1align-2×j=1nB12πdetΣBfalse(λ1,2false)exp12W1Bj(λ1…”
Section: Delta‐based Box‐cox Approachmentioning
confidence: 99%
“…The size is very close to the true nominal level in all cases (see Table 1 in Web Appendix A). We compared the delta‐based approach where the distributional assumptions are correct, under the same setting, with the approach of Dong et al, which is based on generalized pivots (see Table 2 in Web Appendix A). We observed that the proposed method consistently outperforms the generalized pivot‐based approach in terms of size.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 2 more Smart Citations